2015
DOI: 10.1101/025973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing RADseq and microsatellites to infer complex phylogeographic patterns, a real data informed perspective in the Crucian carp,Carassius carassius, L

Abstract: The conservation of threatened species must be underpinned by phylogeographic knowledge in order to be effective. This need is epitomised by the freshwater fish Carassius carassius, which has recently undergone drastic declines across much of its European range. Restriction Site Associated DNA sequencing (RADseq) is being increasingly used for such phylogeographic questions, however RADseq is expensive, and limitations on sample number must be weighed against the benefit of large numbers of markers. Such trade… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…The crucian carp might be assumed to have negative impacts on pond biodiversity by having "carp" in its name and likely being non-native (Jeffries et al, 2017). Foraging activities of introduced common carp are known to reduce invertebrate density and macrophyte cover, with knock-on effects for amphibian and waterfowl species richness and abundance (Chan, 2011;Haas et al, 2007;Maceda-Veiga et al, 2017).…”
Section: Impact Of Crucian Carp Stocking On Pond Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucian carp might be assumed to have negative impacts on pond biodiversity by having "carp" in its name and likely being non-native (Jeffries et al, 2017). Foraging activities of introduced common carp are known to reduce invertebrate density and macrophyte cover, with knock-on effects for amphibian and waterfowl species richness and abundance (Chan, 2011;Haas et al, 2007;Maceda-Veiga et al, 2017).…”
Section: Impact Of Crucian Carp Stocking On Pond Invertebratesmentioning
confidence: 99%
“…A key objective of this BAP is to increase the number of viable crucian carp populations across Norfolk through pond restoration and species reintroduction. Many Norfolk ponds have since been restored and stocked with crucian carp to realise this objective (Sayer et al, 2020), but maintaining populations and continued stocking requires justification in light of genetic evidence that indicates the crucian carp is not native to the UK (Jeffries et al, 2017). Nonetheless, there is support for UK conservation efforts to continue to protect the genetic integrity of the crucian carp at the European level, and provide a natural stronghold for the species Jeffries et al, 2017;Stefanoudis et al, 2017) in the face of persistent declines throughout its native range of Northwest and Central Europe (Copp et al, 2008;Sayer et al, 2011;Sayer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative breeding programs that wish to partner with academic or commercial laboratories to generate molecular data should insure that SNP data, rather than microsatellite data, will be collected. Numerous methods for generating large panels of SNPs currently exist, but the most efficient and economical option for many zoo and aquarium populations at this time is restriction site‐associated DNA (RAD) sequencing (Davey & Blaxter, ; Jeffries et al, ; Peterson, Weber, Kay, Fisher, & Hoekstra, ; Hoffberg et al, ). Alternatively, full or partial genome sequencing of a small number of individuals can be used to first identify SNPs and then design an assay to subsequently generate data across a population (e.g., Norman, Street, & Spong, ), but this approach requires more resources initially and thus may be more expensive.…”
Section: Case Studymentioning
confidence: 99%
“…The current study included relatively few individuals (n = 23) compared to many traditional population genetics studies; however, recent studies have shown that larger sets of markers can overcome low sample sizes in population studies[53]. In Crucian carp, Carassius carassius , the authors demonstrated that RAD-tag markers were able to detect finer structure among populations than microsatellites (13,189 SNPs vs. 13 microsatellites), despite including only 17.6% of the individuals genotyped with microsatellites (n = 848 with microsatellites, n = 149 with SNPs) [54]. The use of large sets of SNPs can detect structure in even smaller sample sizes.…”
Section: Discussionmentioning
confidence: 99%